Constructing HEIs Performance - Nugroho Prasetyo Aditama (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study analyses how higher education institutions (HEIs) performance is constructed within the 2020–2021 Merdeka Belajar-Kampus Merdeka (MBKM) policy, within the context of the strengthening of neoliberal ideology in Indonesian higher education. Using Norman Fairclough's critical discourse analysis approach, this study examines five policy documents and elaborates on them with interviews with five MBKM student participants. NVIVO was used as a tool to facilitate in-depth analysis of the analysed aspects. The results show that the MBKM policy frames HEIs as institutions that support economic growth through discursive representations that emphasise neoliberal logic, such as efficiency, competitiveness, and industrial relevance. Terms such as